Corundum mullite silicon nitride brick for garbage incinerator and preparation method of corundum mullite silicon nitride brick

By using corundum mullite silicon nitride bricks composed of dense corundum, silicon nitride and high purity mullite, the problem of high requirements for the comprehensive performance of refractory materials by waste incinerators is solved, and high wear resistance, corrosion resistance, thermal shock stability and environmental protection and economical effects are achieved.

CN119775034AActive Publication Date: 2025-04-08河南瑞泰耐火材料科技有限公司
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411890198.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-08
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

Waste incinerators have high requirements for the comprehensive performance of refractory materials, including high wear resistance, corrosion resistance, thermal shock stability, etc., and require environmental protection and economicality.

Method used

Corundum mullite silicon nitride bricks composed of dense corundum, silicon nitride and high purity mullite are used, and sulfite waste liquid is added as a binding agent through specific ratios and preparation methods to form high-performance refractory materials.

Benefits of technology

This material has high wear resistance, corrosion resistance, good thermal shock stability, and has a small volume density. It can replace some aluminum-chromium bricks, reduce the pollution of hexavalent chromium to the environment, and has good environmental protection and economicality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005200470020000081
    Figure BDA0005200470020000081
Patent Text Reader

Abstract

The invention discloses a corundum mullite silicon nitride brick for a garbage incinerator and a preparation method of the corundum mullite silicon nitride brick. The corundum mullite silicon nitride brick is composed of 6 to 10% of compact corundum with a particle size of 5 to 3 mm, 18 to 22% of compact corundum with a particle size of 3 to 1 mm, 14 to 18% of compact corundum with a particle size of 1 to 0 mm, 12 to 16% of high-purity mullite with a particle size of 3 to 1 mm, 8 to 12% of high-purity mullite with a particle size of 1 to 0 mm, 18 to 22% of compact corundum with a particle size of less than 0.088 mm, 4 to 8% of high-purity mullite with a particle size of less than 0.088 mm, and 4 to 8% of silicon nitride with a particle size of 325 meshes. In addition, a binding agent accounting for 3-4% of the total weight of all the raw materials is added. Firstly, aggregate is mixed, then a binding agent is added for continuous mixing, then powder is added for continuous mixing, and a mixed material is obtained; and pressing the obtained mixed material into a green brick, drying the green brick, sintering, and cooling to obtain the product corundum mullite silicon nitride brick. The prepared product is small in volume density, high in strength, good in abrasion resistance, excellent in erosion resistance, good in thermal shock stability, environmentally friendly, capable of saving energy and capable of completely meeting the use requirements of the garbage incinerator in different environments.
Need to check novelty before this filing date? Find Prior Art

Description

1. Technical field:

[0001] The invention belongs to the technical field of refractory materials, and particularly relates to a corundum-mullite silicon nitride brick for a garbage incinerator and a preparation method thereof. 2. Background technology:

[0002] Waste incinerators usually need to use refractory materials to protect the furnace structure from high temperature and corrosive gases such as cysteine. Selecting the right refractory material is very important for the life of the waste incinerator and improving its performance.

[0003] When the incinerated garbage is a heterogeneous mixture of different compositions, its type, quantity and calorific value are also very different. For this reason, the physical and chemical properties of the lining should be adapted to the requirements of different stages during operation. The operating temperature of a garbage incinerator generally does not exceed 1200°C, but the complex working environment (such as gas erosion, wear and impact of garbage on the inside of the furnace during high-temperature movement) requires the use of refractory linings with better performance, and the demand will continue to increase.

[0004] In a waste incinerator, the input and fall of waste will cause wear and impact on the inside of the furnace body, requiring the refractory material to have good wear resistance and strength. Waste will produce corrosive gases at high temperatures, so the refractory material must also have corrosion resistance. The temperature in the incinerator fluctuates greatly, requiring the refractory material to have good thermal shock resistance. In addition, considering the environmental protection and economy of the material, the refractory material is also required to have good environmental protection and energy saving. 3. Summary of the invention:

[0005] The technical problem to be solved by the present invention is: in view of the comprehensive requirements of waste incinerators for various aspects of the performance of the refractory materials used, the present invention provides a corundum-mullite silicon nitride brick for waste incinerators with the characteristics of high wear resistance, corrosion resistance, good thermal shock stability, etc. and a preparation method thereof. The corundum-mullite silicon nitride brick for waste incinerators prepared by the technical solution of the present invention has the characteristics of high wear resistance, corrosion resistance, good thermal shock stability, etc.; at the same time, the corundum-mullite silicon nitride brick of the present invention has a small volume density, can replace a part of the aluminum-chrome bricks currently in common use, is more economical, and can reduce the pollution of the environment caused by the conversion of trivalent chromium into hexavalent chromium, which is beneficial to environmental protection.

[0006] In order to solve the above problems, the technical solution adopted by the present invention is:

[0007] The invention provides a corundum-mullite silicon nitride brick for a garbage incinerator. The corundum-mullite silicon nitride brick mainly consists of aggregate and powder, expressed in weight percentage. The aggregate consists of 6-10% of dense corundum with a size of 5-3 mm, 18-22% of dense corundum with a size of 3-1 mm, 14-18% of dense corundum with a size of 1-0 mm, 12-16% of high-purity mullite with a size of 3-1 mm and 8-12% of high-purity mullite with a size of 1-0 mm. The powder consists of 18-22% of dense corundum with a size of less than 0.088 mm, 4-8% of high-purity mullite with a size of less than 0.088 mm and 4-8% of silicon nitride with a particle size of 325 mesh. In addition, a binder accounting for 3-4% of the total weight of the aggregate and the powder is added.

[0008] According to the above-mentioned corundum-mullite silicon nitride brick for a waste incinerator, the Al2O3 content in the dense corundum is ≥98.5%, and the SiO2 content is ≤0.5%.

[0009] According to the above-mentioned corundum-mullite silicon nitride brick for a waste incinerator, the Al2O3 content in the high-purity mullite is ≥70%, and the SiO2 content is ≤28%.

[0010] According to the above-mentioned corundum-mullite silicon nitride brick for a waste incinerator, the Si3N4 content in the silicon nitride is ≥99%.

[0011] According to the above-mentioned corundum mullite silicon nitride bricks for waste incinerators, the binder is sulfite pulp waste liquid, and its specific gravity is 1.24-1.28.

[0012] In addition, a method for preparing corundum-mullite silicon nitride bricks for a waste incinerator is provided, the preparation method comprising the following steps:

[0013] a. Mixing: First, weigh various raw materials according to the ratio of the above-mentioned corundum mullite silicon nitride bricks, add the weighed aggregate into a mixer and mix (mixing time is 1 to 2 minutes), then add a binder and continue mixing (mixing time is 2 to 3 minutes), then add powder and continue mixing (mixing time is 5 to 10 minutes) to obtain a mixed material;

[0014] b. Forming: The obtained mixed material is pressed into a brick by a press;

[0015] c. Drying: drying the obtained bricks;

[0016] d. The dried bricks are placed in a high-temperature tunnel kiln for firing, and then cooled to obtain the product corundum mullite silicon nitride bricks for waste incinerators.

[0017] According to the preparation method of corundum mullite silicon nitride bricks for waste incinerators, during the pressing and molding in step b, the pressure of the press is controlled to be 630 to 1000 tons; the volume density of the obtained brick is controlled to be 2.92 to 2.95 g / cm 3 .

[0018] According to the preparation method of the corundum-mullite silicon nitride brick for the waste incinerator, a dryer is used for drying in step c, the temperature of the dryer is controlled at 110-130° C., and the residual moisture in the brick after drying is ≤0.5%.

[0019] According to the above-mentioned method for preparing corundum mullite silicon nitride bricks for waste incinerators, during the firing in step d, the firing temperature is 1600-1630° C., and the insulation time at the firing temperature is 4-6 hours.

[0020] The positive beneficial effects of the present invention are:

[0021] 1. The Si3N4 fine powder added to the corundum mullite silicon nitride brick composition of the present invention can improve the wear resistance of the product because silicon nitride is hard and belongs to high-hardness refractory materials with high mechanical strength and strong wear resistance, and can well resist the wear and impact of the input and fall of waste on the furnace body. Secondly, silicon nitride has good antioxidant properties and strong acid and alkali corrosion resistance, which is more suitable for the complex atmosphere environment of waste incinerators. In addition, Si3N4 has a low expansion coefficient, is not easy to produce thermal stress, has excellent thermal shock resistance and stability, and is suitable for long-term use at high temperatures.

[0022] 2. In the composition of the corundum-mullite silicon nitride brick of the present invention, dense corundum is added, because the hardness of dense corundum is relatively large, which can improve the wear resistance of the product. At the same time, high-toughness refractory high-purity mullite is added, and the unique layered structure of mullite can effectively fill the gaps between corundum particles, enhance the overall density of the material, thereby reducing cracks and pores, and improving strength and stability. Secondly, the solid interface formed between mullite and corundum greatly enhances the interface stability of the material and effectively resists the generation of interface cracks. Furthermore, mullite has a lower thermal expansion coefficient, which can form a good complement with the high thermal expansion coefficient of corundum, absorb part of the thermal expansion stress, reduce the internal stress caused by thermal expansion, and then reduce the risk of rupture. Finally, by adding mullite, the thermal conductivity of corundum bricks can be accurately regulated, the heat conduction speed can be slowed down, and the accumulation and propagation of thermal shock stress can be effectively reduced, thereby comprehensively improving the thermal shock resistance of corundum-mullite silicon nitride bricks, and the corundum-mullite phase has certain resistance to alkali erosion and carbon monoxide erosion. Therefore, the product prepared by the present invention has the advantages of good thermal shock stability, chemical corrosion resistance, wear resistance and atmosphere change resistance, and has a wider range of applications. It can be applied to non-uniform garbage mixtures of different types and different components in garbage incinerators to exert its excellent properties.

[0023] 3. The corundum-mullite silicon nitride brick prepared by the technical solution of the present invention has a small volume density and does not contain chromium, which can effectively reduce the pollution of hexavalent chromium to the environment, is beneficial to environmental protection, and has good economic efficiency.

[0024] 4. The relevant performance parameters of the corundum-mullite silicon nitride bricks for waste incinerators prepared by the technical solution of the present invention are shown in Table 1.

[0025] Table 1 Corundum mullite silicon nitride bricks for waste incinerators of the present invention

[0026] Test items Standard value Bulk density (g / cm3) 2.92-2.95 Apparent porosity (%) 17-19 Normal temperature compressive strength (Mpa) >100 Softening temperature under load(℃) >1700 Thermal shock stability (1100℃ water cooling times) >25 <![CDATA[Wear resistance (cm 3 )]]> <3

[0027] In summary, the corundum mullite silicon nitride brick prepared by the technical solution of the present invention has low volume density, high strength, good wear resistance, excellent corrosion resistance, good thermal shock stability, environmental protection and energy saving, and can fully meet the different environmental uses of garbage incinerators. 4. Specific implementation methods:

[0028] The present invention is further described below in conjunction with embodiments, but the protection scope of the technical solution of the present invention is not limited thereto.

[0029] In the following embodiments, the Al2O3 content of the dense corundum used is ≥98.5%, and the SiO2 content is ≤0.5%; the Al2O3 content of the high-purity mullite is ≥70%, and the SiO2 content is ≤28%; the Si3N4 content of the silicon nitride is ≥99%; and the binder is sulfite pulp waste liquid, and its specific gravity is 1.24-1.28.

[0030] Embodiment 1:

[0031] The corundum-mullite silicon nitride brick for a garbage incinerator of the present invention is composed of aggregate and powder, expressed in weight percentage. The aggregate consists of 8% of dense corundum with a size of 5 to 3 mm, 20% of dense corundum with a size of 3 to 1 mm, 16% of dense corundum with a size of 1 to 0 mm, 14% of high-purity mullite with a size of 3 to 1 mm and 10% of high-purity mullite with a size of 1 to 0 mm. The powder consists of 20% of dense corundum with a size of less than 0.088 mm, 6% of high-purity mullite with a size of less than 0.088 mm and 6% of silicon nitride with a particle size of 325 mesh. In addition, sulfite pulp waste liquid, a binder accounting for 3.5% of the total weight of the aggregate and the powder, is added.

[0032] Embodiment 2:

[0033] The corundum-mullite silicon nitride brick for a garbage incinerator of the present invention is composed of aggregate and powder, expressed in weight percentage. The aggregate consists of 7% of dense corundum with a size of 5 to 3 mm, 21% of dense corundum with a size of 3 to 1 mm, 15% of dense corundum with a size of 1 to 0 mm, 13% of high-purity mullite with a size of 3 to 1 mm and 11% of high-purity mullite with a size of 1 to 0 mm. The powder consists of 21% of dense corundum with a size of less than 0.088 mm, 5% of high-purity mullite with a size of less than 0.088 mm and 7% of silicon nitride with a particle size of 325 mesh. In addition, sulfite pulp waste liquid, a binder accounting for 3.5% of the total weight of the aggregate and the powder, is added.

[0034] Embodiment 3:

[0035] The corundum-mullite silicon nitride brick for a garbage incinerator of the present invention is composed of aggregate and powder, expressed in weight percentage. The aggregate consists of 10% of dense corundum with a size of 5 to 3 mm, 18% of dense corundum with a size of 3 to 1 mm, 17% of dense corundum with a size of 1 to 0 mm, 15% of high-purity mullite with a size of 3 to 1 mm and 11% of high-purity mullite with a size of 1 to 0 mm. The powder consists of 19% of dense corundum with a size of less than 0.088 mm, 5% of high-purity mullite with a size of less than 0.088 mm and 5% of silicon nitride with a particle size of 325 mesh. In addition, sulfite pulp waste liquid, a binder accounting for 3.5% of the total weight of the aggregate and the powder, is added.

[0036] Embodiment 4:

[0037] The corundum-mullite silicon nitride brick for a garbage incinerator of the present invention is composed of aggregate and powder, expressed in weight percentage. The aggregate consists of 6% of dense corundum with a size of 5 to 3 mm, 22% of dense corundum with a size of 3 to 1 mm, 14% of dense corundum with a size of 1 to 0 mm, 16% of high-purity mullite with a size of 3 to 1 mm and 8% of high-purity mullite with a size of 1 to 0 mm. The powder consists of 22% of dense corundum with a size of less than 0.088 mm, 5% of high-purity mullite with a size of less than 0.088 mm and 7% of silicon nitride with a particle size of 325 mesh. In addition, sulfite pulp waste liquid, a binder accounting for 3.5% of the total weight of the aggregate and the powder, is added.

[0038] The preparation method of the corundum-mullite silicon nitride brick for the garbage incinerator described in Examples 1 to 4 of the present invention comprises the following detailed steps:

[0039] a. Mixing: First, various raw materials are weighed according to the proportion of the corundum mullite silicon nitride bricks described in any one of Examples 1 to 4, and the weighed aggregate is added to a mixer and mixed for 2 minutes, then a binder is added and mixed for 3 minutes, and then the powder is added and mixed for 6 minutes to obtain a mixed material;

[0040] b. Molding: The obtained mixed material is pressed into a brick by a press, and the pressure of the press is controlled to be 650-700 tons. The volume density of the obtained brick is 2.92-2.95 g / cm 3 ;

[0041] c. Drying: The obtained bricks are placed in a dryer for drying. The temperature of the dryer is controlled at 110-130°C. After drying, the residual moisture in the bricks is ≤0.5%;

[0042] d. The dried bricks are placed in a high-temperature tunnel kiln for firing at a temperature of 1600-1630°C. The holding time at the firing temperature is 6 hours. After firing, the bricks are cooled to obtain the product of corundum mullite silicon nitride bricks for waste incinerators.

[0043] Comparative Example 1:

[0044] A corundum-mullite silicon nitride brick for a garbage incinerator, expressed in weight percentage, the raw material composition is:

[0045] Aggregate composition: 8% dense corundum of 5-3mm, 20% dense corundum of 3-1mm, 26% dense corundum of 1-0mm and 14% high-purity mullite of 3-1mm;

[0046] Powder composition: 20% dense corundum <0.088mm, 6% high-purity mullite <0.088mm and 6% silicon nitride with a particle size of 325 mesh;

[0047] In addition, sulfite pulp waste liquor, a binder, was added in an amount of 3.5% by weight of the total weight of all the above raw materials.

[0048] In the raw material composition of Comparative Example 1, no 1-0 mm high-purity mullite is added.

[0049] Comparative Example 2:

[0050] A corundum-mullite silicon nitride brick for a garbage incinerator, expressed in weight percentage, the raw material composition is:

[0051] Aggregate composition: 8% dense corundum of 5-3mm, 34% dense corundum of 3-1mm, 16% dense corundum of 1-0mm and 10% high-purity mullite of 1-0mm;

[0052] Powder composition: 20% dense corundum <0.088mm, 6% high-purity mullite <0.088mm and 6% silicon nitride with a particle size of 325 mesh;

[0053] In addition, sulfite pulp waste liquor, a binder, was added in an amount of 3.5% by weight of the total weight of all the above raw materials.

[0054] In the raw material composition of Comparative Example 2, no 3-1 mm high-purity mullite is added.

[0055] Comparative Example 3:

[0056] A corundum-mullite silicon nitride brick for a garbage incinerator, expressed in weight percentage, the raw material composition is:

[0057] Aggregate composition: 8% dense corundum of 5-3mm, 20% dense corundum of 3-1mm, 16% dense corundum of 1-0mm, 14% high-purity mullite of 3-1mm and 10% high-purity mullite of 1-0mm;

[0058] Powder composition: 26% of dense corundum <0.088mm and 6% of high-purity mullite <0.088mm;

[0059] In addition, sulfite pulp waste liquor, a binder, was added in an amount of 3.5% by weight of the total weight of all the above raw materials.

[0060] In the raw material composition of Comparative Example 3, 325 mesh silicon nitride is not added.

[0061] The preparation method of the corundum mullite silicon nitride brick for the garbage incinerator described in Comparative Examples 1 to 3 is the same as the preparation method of Examples 1 to 4 of the present invention.

[0062] The relevant performance data comparison of the products prepared in Examples 1 to 4 of the present invention and Comparative Examples 1 to 3 are shown in Table 2.

[0063] Table 2 Relevant performance data of the products prepared in Examples 1 to 4 of the present invention and Comparative Examples 1 to 3

[0064]

[0065] It can be seen from the relevant performance test data of the corundum-mullite silicon nitride products prepared by the embodiments of the present invention and the comparative examples in Table 2 that the corundum-mullite silicon nitride bricks prepared by the technical solution of the present invention have low volume density, high strength, good wear resistance, excellent corrosion resistance, good thermal shock stability, environmental protection and energy saving, and can fully meet the different environmental uses of waste incinerators.

Claims

1. A corundum-mullite silicon nitride brick for a waste incinerator, characterized in that: Expressed in weight percentage, the corundum-mullite silicon nitride brick is mainly composed of aggregate and powder, the aggregate is composed of 6-10% of dense corundum of 5-3mm, 18-22% of dense corundum of 3-1mm, 14-18% of dense corundum of 1-0mm, 12-16% of high-purity mullite of 3-1mm and 8-12% of high-purity mullite of 1-0mm, the powder is composed of 18-22% of dense corundum of raw material <0.088mm, 4-8% of high-purity mullite <0.088mm and 4-8% of silicon nitride with a particle size of 325 mesh; in addition, a binder accounting for 3-4% of the total weight of the aggregate and the powder is added.

2. The corundum-mullite silicon nitride brick for a waste incinerator according to claim 1, characterized in that: The Al2O3 content in the dense corundum is ≥98.5%, and the SiO2 content is ≤0.5%.

3. The corundum-mullite silicon nitride brick for a waste incinerator according to claim 1, characterized in that: The Al2O3 content in the high-purity mullite is ≥70%, and the SiO2 content is ≤28%.

4. The corundum-mullite silicon nitride brick for a waste incinerator according to claim 1, characterized in that: The Si3N4 content in the silicon nitride is ≥99%.

5. The corundum-mullite silicon nitride brick for a waste incinerator according to claim 1, characterized in that: The binder is sulfite pulp waste liquid, and its specific gravity is 1.24-1.

28.

6. A method for preparing corundum mullite silicon nitride bricks for waste incinerators, characterized in that: The preparation method comprises the following steps: a. Mixing: First, various raw materials are weighed according to the ratio of the corundum mullite silicon nitride bricks according to claim 1, the weighed aggregates are added to a mixer for mixing, then a binder is added and the mixing is continued, and then the powder is added and the mixing is continued to obtain a mixed material; b. Forming: The obtained mixed material is pressed into a brick by a press; c. Drying: drying the obtained bricks; d. The dried bricks are placed in a high-temperature tunnel kiln for firing, and then cooled to obtain the product corundum mullite silicon nitride bricks for waste incinerators.

7. The method for preparing corundum-mullite silicon nitride bricks for waste incinerators according to claim 6, characterized in that: During the pressing process in step b, the pressure of the press is controlled to be 630-1000 tons; the bulk density of the obtained brick is controlled to be 2.92-2.95 g / cm 3 .

8. The method for preparing corundum-mullite silicon nitride bricks for waste incinerators according to claim 6, characterized in that: The drying in step c is performed using a dryer, the temperature of the dryer is controlled at 110-130° C., and the residual moisture in the bricks after drying is ≤0.5%.

9. The method for preparing corundum-mullite silicon nitride bricks for waste incinerators according to claim 6, characterized in that: During the sintering in step d, the sintering temperature is 1600-1630° C., and the holding time at the sintering temperature is 4-6 hours.

Citation Information

Patent Citations

  • Lightweight siliceous mullite composite brick and preparation method thereof

    CN103755363A

  • Stone brick for garbage incinerator and preparation method thereof

    CN103803992A

  • Corundum-mullite composite brick for COREX furnace and preparation method thereof

    CN103880447A

  • Corundum-mullite burnt brick applied to gas turbine combustion chamber and preparation method thereof

    CN104803692A

  • High-strength and wear-resistant chromium corundum-mullite-Si3N4 plastic refractory for target zone of cyclone separator of CFB boiler

    CN107556005A